2009
DOI: 10.1039/b812423j
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystal elastomer–nanoparticle systems for actuation

Abstract: Liquid crystal elastomers (LCE) are currently of great interest due to conjoining of mesogenic ordering and rubber elasticity, exhibited in their large spontaneous thermally stimulated changes in shape. It has been shown that nanoparticles (nanotubes, photo-isomerisable dyes, magnetic nanoparticles.) can be incorporated into these LCE networks to create a more sensitive network to external stimuli (i.e. strain or stress, optical, electrical, electro-thermal, magnetic.). Here, we briefly summarise the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 43 publications
1
81
0
1
Order By: Relevance
“…This method also faces critical heat transfer problems. A thin layer of conducting carbon on the LCE surface has the same shortcoming, with loss of mechanical response [42][43][44][45][46].…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…This method also faces critical heat transfer problems. A thin layer of conducting carbon on the LCE surface has the same shortcoming, with loss of mechanical response [42][43][44][45][46].…”
Section: Open Accessmentioning
confidence: 99%
“…Studies of the electromechanical actuation of these materials have not yet been attempted. Since electromechanical actuation induced by a conducting layer due to Joule heating has been reviewed in [43], we here focus our attention on another mechanism, that is, the actuation due to electrostatic fields. Such actuation was demonstrated using mono-domain LCEs with CNTs [53].…”
Section: Electrical Actuationmentioning
confidence: 99%
“…With inclusion of carbon black (CB) nanoparticles, Chambers et al developed electrically conductive LCE/CB nanocomposites. [ 17 ] By passing electric currents, the temperature of LCE/CB can be increased to initiate the shape change. Similar approach was taken by Yang et al [ 18 ] and Kohlmeyer and Chen [ 19 ] to prepare LCE/SWCNT (single-walled carbon nanotubes) nanocomposites with very low SWCNT loading (0.1-0.2 wt%).…”
Section: Introductionmentioning
confidence: 99%
“…1 This ability makes LCEs attractive candidates for a variety of applications in robotics, photonics, and microfluidics. It has been demonstrated that modified LCEs can exhibit thermal, 2-5 electrical, 6 and photo-induced 7,8 actuation; based on these achievements, a number of devices such as microvalves, 9 optical tweezers, and microgrippers 10 among others have been reported. Photo-induced actuation in particular is attractive because it can be triggered by an external "remote" stimulus (rather than by direct heating, which is inconvenient for most practical applications) and because the speed and periodicity of the stimulus can be finely controlled.…”
mentioning
confidence: 99%